Bioremediation of petroleum sludge using effective microorganism (EM) technology. (18th July 2017) - Ahmad, Jamil
ABSTRACT: A study was designed for the bioremediation of waste sludge from a petroleum refinery applying effective microorganism (EM) technology. The treated sludge was found rich in organic matter, nitrogen, phosphorus, potassium (N, P, K) and was mixed with clean soil (1:1) to prepare a product named as EM biofertilizer. The EM biofertilizer was compared with FYM. It was shown that the field using EM biofertilizer given 275 kg yield compare to the 230 kg yield obtained with farm yard manure (FYM). The quantity of heavy metals in onion using EM biofertlizer was all within the EU 2006 permissible limits.